Generativity versus Stagnation”: Midlife Crisis in Kazuo Ishiguro’s The Remains of the Day - JAFARI, Morteza; MOTALLEBZADEH, Naser; DASHTPEYMA, Naser (Anafora, 2023)
This paper discusses midlife crisis as a driving force behind the thought and action of the protagonist of Kazuo Ishiguro’s The Remains of the Day. The whole novel contains a diary written by the English butler Stevens who relates his history of servitude at Darlington Hall and concludes with some revelations about the true nature of his past. Since the butler’s account gives hints of his concern for the extent of hisachievement in life, his reassessing act of delving into the past can be taken as an attempt to resolve his midlife crisis. Being the seventh stage of Erik Erikson’s developmental psychology, a midlife crisis is primarily characterized by the binary “generativity versus stagnation” and the subject’s struggle to decide on the meaning of life. Occurring between 40 and 65, midlife crisis is stimulated by the reconsideration of social demands such as career and marriage. Applying this psychoanalytic approach to Stevens’ experience of midlife crisis, the present research investigates the place of Lord Darlington and Miss Kenton, the former Stevens’ employer and the latter his only love object, as embodiments of the social demands of career and marriage that the butler reviews in his midlife stage. Ultimately, this research discusses the butler’s success in resolving his midlife crisis through considering the individuation process, namely self-awareness, self-actualization, and the caring power, which the protagonist goes through.